The incidence of Lower (UTI) according to the age and sex in Ramadi City. - Abdullah, Essam M.; Mutlak, Saad T. (Journal of the Faculty of Medicine Baghdad, 2009)
Back ground: A urinary tract infection is one of the most common diseases occurring from neonate up to geriatric age groupsPatients and Methods: A total of (100) Midstream urine (MSU) samples were collected from patients having signs and symptoms of Lower urinary tract infection. These patients were attending Urology Clinic, Ramadi General Hospital.Result: Culturing of (100) MSU samples on MacConky and blood agar resulted in (5) types of bacteria which included: Escherichia coli (46%) and it was found the most frequent bacteria causing LUTI. This is followed by Klebsiella pneumonia (23%), Pseudomonas aeruginosa (13%), Proteus mirabilis (10%) and Staphylococcus epidermidis (8%).Conclusion: Out of the total studied samples, (38%) were males and (62%) were females. It was found that the age of frequent infection was 60 year in male, while in female was 16-35 year.